Opening-up Trajectories and Economic Recovery : Lessons after the First Wave of the COVID-19 Pandemic - Demirguc-Kunt, Asli; Lokshin, Michael; Torre, Ivan (World Bank, Washington, DC, 2020)
This paper analyzes the reopening process of countries in Europe and Central Asia after the first wave of the COVID-19 pandemic and provides evidence on the effects of different reopening trajectories and their timing and speed on economic recovery. The analysis indicates that countries that adopted a gradual, staged reopening experienced stronger economic recovery compared with the countries that rushed into lifting the restrictive measures before the pandemic was under control. Postponing lifting the restrictions until after the pandemic's peak was reached has a positive impact on economic activity. Governance also matters: a higher level of trust in government is associated with increased economic activity among countries that carried out a gradual reopening process. There is also suggestive evidence that providing people objective data on the progress of the pandemic may speed up the recovery process.